Research progress in lateral lymph node dissection for rectal cancer - Dong, Miao-Miao; Qian, Zheng-peng; Lu, Ji-Yong; Li, Jing-Jing; lv, Yao-Chun; Xu, Shi-Yun; Du, Bin-Bin; Wu, De-Wang (Frontiers in Oncology, 2025)
Lateral lymph node dissection (LLND), a critical surgical intervention for patients with low rectal cancer, plays a pivotal role in clinical practice. Its primary objective is to completely resect lateral pelvic lymph nodes, block the metastatic pathway of tumor cells, minimize the risk of postoperative recurrence, and provide a foundation for long-term survival. In Japan, LLND has become a standard surgical procedure for low rectal cancer and is widely applied. However, in Europe and North America, neoadjuvant chemoradiotherapy (nCRT) is regarded as the dominant treatment standard, which has led LLND to remain controversial and face doubts in clinical application. This article integrates the latest clinical research findings, explores the trajectory of technical evolution, analyzes clinical efficacy, objectively presents key points of academic controversy, and prospectively considers future developments. It aims to provide a comprehensive professional analysis for the rational application and continuous optimization of this technique in the treatment of low rectal cancer.